Iliopsoas pathology, treatment, and outcomes in patients undergoing hip arthroscopy for femoroacetabular impingement: Findings from the [redacted] study group. Issue 7 (31st July 2020) - Kivlan, Benjamin; Nho, Shane; Wolff, Andrew; Salvo, John; Christoforetti, John; Ellis, Thomas; Carreira, Dominic; Matsuda, Dean
Paste abstract here and remove the remaining text. *For structured abstracts, begin each section under a separate, bolded subheading. Suggested subheadings are below Objectives: The iliopsoas is a major hip flexor that provides anterior hip stability. Recent studies report significant compromise to these important functions with iliopsoas tenotomy. The purpose of this study is to report the prevalence, associated findings, rendered procedures, and outcomes of hips with iliopsoas involvement undergoing hip arthroscopy for FAI and/or chondrolabral pathology. The hypothesis is that there is a decrease in the incidence of tenotomy compared with historic controls and that tenotomy compromises patient-reported outcomes. Methods: Level of evidence 3 controlled study with prospectively-collected multicenter database from 7 centers. Enrolled patients that underwent isolated hip arthroscopy that reached 2-year minimum follow-up with iHOT-12 were assigned to Iliopsoas group defined as pre-operative diagnosis of iliopsoas tendonitis, internal snapping symptoms, intra-operative anteroinferior labral pathology (below 3 O'clock location) and/or preoperative psoas injection or the control group. The prevalence of iliopsoas pathology, radiographic and intra-operative findings, and rendered procedures between groups were compared using Chi square analysis. Minimum 2-year outcomes of Iliopsoas group versus control group were compared using analysis of variance (a priori alpha set at 0.05). Subanalysis within the Iliopsoas group was performed of patients with versus without tenotomy. Results: There were 97 study group subjects and 1053 control group subjects. There was no statistical difference in demographics between the groups (p>0.05) nor was there a difference in length of preoperative symptom duration (p=0.51). There were no significant differences in the incidence of cam impingement, pincer impingement or dysplasia between cohorts, nor were there significant differences between radiographic measures. There was a similar incidence of femoroplasty, acetabuloplasty, chondroplasty, microfracture, and synovectomy (p>0.05) regardless of iliopsoas involvement. There was not a significant effect on the surgical treatment of the labrum based on psoas involvement (p>0.16). Labral repair was performed in 55% of patients with iliopsoas involvement and 62% of patients without iliopsoas involvement. Although there was not a significant difference in capsular closure between cohorts (96% vs 93%, p=0.121), the overwhelming majority of patients with psoas involvement received capsular repair (87%) or plication (9%). Pre-operative iHOT-12 scores were similar 34 (SD: 18) for the iliopsoas group and 35 (SD 18) for the control group groups (p=0.51). Post-operative iHOT-12 scores improved to 72 for both the groups. The iliopsoas group achieved MCID, SCB, and PASS scores established for the iHOT-12 of 83%, 62%, and 58% which were similar to the control group. Ten subjects (10%) in the iliopsoas group received iliopsoas tenotomy. Subjects with tenotomy had lower 2-year post-op iHOT-12 scores compared to the non-tenotomy subgroup (55 vs 72, respectively; p=0.03) . This corresponded with lower achievement of MCID scores (60% vs 86%; p=0.03) and SCB scores (30% vs 70%, p=0.01) of patients with tenotomy compared to those without tenotomy. Conclusion: Iliopsoas tenotomy is rarely performed relative to its prevalence in patients undergoing hip arthroscopy by high volume surgeons for FAI and/or chondrolabral pathology. Surgical outcomes are not worsened with iliopsoas involvement but are worsened with tenotomy.